2016
DOI: 10.1016/j.jagp.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Reactivity and Cerebrovascular Burden in Late-Life GAD: A Neuroimaging Study

Abstract: Objectives Generalized Anxiety Disorder (GAD) is one of the most prevalent mental disorders in the elderly, but its functional neuroanatomy is not well understood. Given the role of emotion dysregulation in GAD, we sought to describe the neural bases of emotion regulation in late-life GAD by analyzing the functional connectivity (FC) in the Salience Network and the Executive Control Network during worry induction and worry reappraisal. Design, setting and participants Twenty-eight elderly GAD and thirty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…These results seemed to be partially in contrast with a previous study showing the lack of involvement of PFC in suppressing worry in elderly GAD patients86 and in women with GAD 85. Additionally, an fMRI study carried out by Karim et al, 111. exploring ER in a group of elderly GAD patients, showed a positive association between ER and global anxiety in the left parahippocampus, left and right precuneus, and right superior occipital gyrus, as well as a negative association between ER and worry severity in precuneus bilaterally.…”
Section: Methodsmentioning
confidence: 60%
“…These results seemed to be partially in contrast with a previous study showing the lack of involvement of PFC in suppressing worry in elderly GAD patients86 and in women with GAD 85. Additionally, an fMRI study carried out by Karim et al, 111. exploring ER in a group of elderly GAD patients, showed a positive association between ER and global anxiety in the left parahippocampus, left and right precuneus, and right superior occipital gyrus, as well as a negative association between ER and worry severity in precuneus bilaterally.…”
Section: Methodsmentioning
confidence: 60%
“…1 for flow diagram). Of the included records, 35 included structural analyses (Abdallah et al., 2013; Andreescu et al., 2017; Brambilla et al., 2012; Cha et al., 2016a; Cha et al., 2014b; Cha et al., 2016b; Chen and Etkin, 2013; De Bellis et al., 2000, 2002; Etkin et al., 2009; Hettema et al., 2012; Hilbert et al., 2015; Karim et al., 2016; Liao et al., 2013, 2014a, 2014b; Makovac et al., 2016a; Mohlman et al., 2009; Molent et al., 2017; Moon and Jeong, 2015a, 2016, 2017a, 2017b; Moon et al., 2015a, 2014, 2015b; Mueller et al., 2013; Schienle et al., 2011; Strawn et al., 2014, 2013; Terlevic et al., 2013; Tromp et al., 2012; Wang et al., 2016b; Zhang et al., 2011; Zhang et al., 2013), 32 included FC analyses (Andreescu et al., 2015; Andreescu et al., 2014; Buff et al., 2016; Cha et al., 2014a; Cha et al., 2016b; Chen and Etkin, 2013; Cui et al., 2016; Etkin et al., 2010; Etkin et al., 2009; Etkin and Schatzberg, 2011; Fonzo et al., 2014; Greenberg et al., 2013; Hölzel et al., 2013; Laufer et al., 2016; Li et al., 2018; Li et al., 2016; Liu et al., 2015; Makovac et al., 2016b; Makovac et al., 2018; McClure et al., 2007; Mohlman et al., 2017; Monk et al., 2008; Oathes et al., 2015; Pace-Schott et al., 2017; Qiao et al., 2017; Rabany et al., 2017; Roy et al., 2013; Strawn et al., 2012; Toazza et al., 2016; Tromp et al., 2012; Wang et al., 2016a;…”
Section: Resultsmentioning
confidence: 99%
“…To focus the review, neuroimaging results obtained from correlation with questionnaires or behavioural data are not reported here. For this reason, results are omitted from 2 records as the only significant results were found after co-varying neural activity with questionnaire data (Karim et al., 2016; Mohlman et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…63,66 In one of the studies which examined brain activation, 66 the hypothesised difference from controls was seen, with an increase in activation of part of the amygdala, accompanied by a decrease in activation of the dorsal lateral prefrontal cortex in older patients with GAD. Two further studies showed no difference between patients with GAD and controls, 67,68 in brain activation and connectivity. However, in one there was a complex relationship between worry and connectivity, suggesting that connectivity between limbic and cortical areas was maximal at an intermediate level of worry.…”
Section: Specific Issues In Late-life Anxiety Disordersmentioning
confidence: 89%